The Strategy for Use of “Zungenbrecher - Einfach Deutsch Lernen” in Learning German - Anavi, Wilma Prisca; Febriane, Dhania; Putri Kurnia, Amanda; Aprilianah, Jihaan (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2024)
In this era of globalization, there is an urgent need to learn foreign languages. Not only English, which is an international language, but also other foreign languages, including German. According to a Deutsche Welle news article with the topic "Zahl der Deutschlernenden bleibt constant", the number of people learning German remains at 15.4 million. The creation of Zungenbrecher cards aims to improve German speaking skills. The strategy is designed to enrich students' learning experience in understanding and using German effectively. Through a creative and interactive approach, this strategy aims to improve students' German speaking, listening and reading skills. It is hoped that the use of this strategy will boost students' learning motivation and broaden their understanding of German culture. This proposal also includes an implementation plan as well as an evaluation of the strategy to ensure the achievement of the desired learning objectives.